2020
DOI: 10.1017/ice.2020.317
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clinical guidance and rapid molecular pathogen detection on evaluation and outcomes of febrile or hypothermic infants

Abstract: Objective: To quantify the impact of clinical guidance and rapid respiratory and meningitis/encephalitis multiplex polymerase chain reaction (mPCR) testing on the management of infants. Design: Before-and-after intervention study. Setting: Tertiary-care children’s hospital. Patients: Infants ≤90 days old presenting with fever or hypothermia to the emergency department (ED). Methods: The study spanned 3 periods: period 1, January 1, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…Included studies were published between 2002 [ 28 ] and 2021 [ 13 , 25 ]. Eight of eighteen studies were randomised control trials [ 17 , 18 , 19 , 20 , 22 , 23 , 24 , 25 ], three were prospective cohort studies [ 14 , 15 , 26 ], five were retrospective cohort studies [ 8 , 12 , 21 , 27 , 28 ], one was a before and after interventional study [ 16 ], and one was a pragmatic AB single subject study [ 13 ]. The studies were conducted in several different countries, the majority being in the United States [ 8 , 12 , 16 , 18 , 20 , 22 , 24 , 25 , 26 , 27 , 28 ], but also other countries including United Kingdom [ 13 ], Canada [ 17 ], Australia [ 21 ], Belgium [ 14 ], Brazil [ 15 ], Italy [ 19 ] and Turkey [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Included studies were published between 2002 [ 28 ] and 2021 [ 13 , 25 ]. Eight of eighteen studies were randomised control trials [ 17 , 18 , 19 , 20 , 22 , 23 , 24 , 25 ], three were prospective cohort studies [ 14 , 15 , 26 ], five were retrospective cohort studies [ 8 , 12 , 21 , 27 , 28 ], one was a before and after interventional study [ 16 ], and one was a pragmatic AB single subject study [ 13 ]. The studies were conducted in several different countries, the majority being in the United States [ 8 , 12 , 16 , 18 , 20 , 22 , 24 , 25 , 26 , 27 , 28 ], but also other countries including United Kingdom [ 13 ], Canada [ 17 ], Australia [ 21 ], Belgium [ 14 ], Brazil [ 15 ], Italy [ 19 ] and Turkey [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…All included studies were conducted in the ED of a paediatric hospital or within the paediatric population of a general hospital, however, the number of hospitals varied between studies. Fifteen of eighteen studies reported outcomes from the paediatric population only [ 8 , 12 , 13 , 15 , 16 , 17 , 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 , 28 ], and three studies extracted paediatric data from a general hospital [ 14 , 18 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of this concept occurred in a recent study from Crook et al [ 5 ]. In this study, the investigators evaluated the impact of clinical guidance and of a multiplex respiratory PCR and a multiplex PCR for meningitis/encephalitis on clinical outcomes among febrile or hypothermic infants ≤90 days of age presenting to the emergency department.…”
Section: Variability In Clinical Impact Over Time: Implications On Ou...mentioning
confidence: 99%
“…Performing and plotting interrupted time series analysis of respiratory and CNS testing reflected increasing effectiveness over time [ 5 ]…”
Section: Figurementioning
confidence: 99%